Effects of cassava pellets and enzymes addition on growth performance, meat quality, serum biochemical indices and cecum microbiota of broilers - Dan Yue; Ying Lu; Jin Zhao; Xiaoming He; Junhong Zhu; Jiawei Liang; Weidong Deng (Poultry Science)
The composition of feed significantly influences the growth performance and gut microbiota of broiler chicks, impacting their overall health and productivity. This study aimed to investigate the effects of cassava pellets and enzymes supplementation on the growth performance, meat quality, serum biochemical indices, and cecal microbial community of broiler chicks. A total of 144 healthy 1-day-old AA broilers were randomly assigned to six dietary groups: basal diet (K1), basal diet + 5 % cassava pellets (K2), basal diet + 10 % cassava pellets (K3), basal diet + 20 % cassava pellets (K4), basal diet + 20 % cassava pellets + 0.3 % tannase (K5), and basal diet + 20 % cassava pellets + 0.3 % tannase + 2500 U/kg α-amylase (K6). At 21 days, growth performance, meat quality, serum biochemical indices, and cecal microbial composition were analyzed. Compared to K1, the end weight was significantly higher in the K3 and K5 groups (P < 0.05); average daily weight gain was significantly higher in the K3 and K6 groups (P < 0.05); and the feed-to-weight ratio was lower in the K3 group (P < 0.05). Cecal microbiota analysis revealed that the Bacteroidetes, Firmicutes, and Proteobacteria were the dominant phyla. Alpha diversity showed a significant increase in the Chao index in the K3 group and in the Shannon and Simpson indices in the K6 group compared to the K1 group (P < 0.05). Beta diversity indicated similar microbial compositions across groups. LEfSe analysis showed increased numbers of specific bacteria in treated groups. Serum analysis revealed significantly higher ALT levels in the K4 group and higher IBIL levels in the K5 group (P < 0.05), with Bacteroides plebeius and Megamonas positively correlated with ALT (P < 0.05). The addition of 10 % cassava pellets to the diet improved the growth performance and meat quality of broilers from 1 to 21 days of age and enhanced the microbial composition, providing valuable insights for optimizing broiler diets and improving economic returns.